دور مواقع التواصل الاجتماعي في التوعية الدينية الفيس بوك أنموذجا - عمامرة, آسماء (University of Eloued جامعة الوادي, 2017)
- هدفت هذه الدراسة إلى التعرف على دور مواقع التواصل الاجتماعي في التوعية الدينية ولتحقيق هذا الهدف تم استخدام المنهج الوصفي لأنه أكثر مناهج البحث ملائمة للمواقع الاجتماعي كسبيل لفهم ظواهره واستخلاص سماته. - تكوّن مجتمع الدراسة من طلبة وطالبات جامعة الوادي المسجلين العام 2016/2017م. وتم اختيار العينة الطبقية قوامها(150) مفردة بمختلف التخصصات. - وكانت أداة الدراسة استبياناً مكوناً من 33 سؤالاً وتوصلت الدراسة إلى مجموعة من النتائج كان من أهمها: 1- بينت الدراسة أن أفراد العينة يستخدمون الفيسبوك بنسبة كبيرة. 2- كون أنّ للفيسبوك دور في توعية الدينية لطلبة الجامعة الوادي إلا أن هذا الدور يبقي متوسطاً في تلقي المعلومات الصادقة عن الدين. 3- هناك وعي متكون لدى عينة من الطلبة الجامعيين من خلال استخدام الفيسبوك وأولى إهماماتهم هو الدفاع عن الدين وتوعية الناس من مخاطر الفيسبوك وكذلك لغرض التحصيل الديني. 4- أن نسبة كبيرة من الطلبة تشجع دور الأسرة في مراقبة أبنائها عند استخدام الفيسبوك. 5- أن نسبة كبيرة من الطلبة أثر الفيسبوك على حياتهم سلباً من ناحية دارستهم وعلاقاتهم الاجتماعية. 6- هناك نسبة كبيرة من الطلبة تعتبر ما تتعرض إليه من مضامين دينية على الفيسبوك لا تحظى بالمصداقية الكافية ما لم تتسم بصدق في منشوراتها. This study aimed to identify the role of social networking sites in religious awareness. To achieve this goal, the descriptive approach was used because it is the most appropriate research method suitable . - The study contains a population of the students of the University of El-oued registered in 2016/2017 and the sample was selected 150 students were selected in different disciplines. -A questionnaire consisting of 33 questions was used a tool. The study reached a number of results, the most important of which were: 1. The study showed that respondents use Face book by a large percentage 2. The fact that Face book plays a role in the religious awareness of the students of the University of the Valley, but this role remains moderate to receive honest information about religion. 3. There is awareness of a sample of university students through the use of Face book and their first interest is to defend religion and raise awareness of the people of the dangers of Face book and also for the purpose of religious collection. 4. That a large percentage of students encourage the role of the family in monitoring their children when using Face book. 5. That a large percentage of students encourage the role of the family in monitoring their children when using Face book and also a large proportion of the students arerejuvenating the family in monitoring their children when using face book. 6. that a large proportion of students Impact Face book on their lives negatively in terms of their studies and social relations and at the same time . Alot of them consider that their religious content on face book is not sufficiently credible unless they are genuinely credi.ble in their publications.
مذكرة ماستر تخصص دعوة واعلام
Keywords: مواقع التواصل الاجتماعي - التوعية الدينية - الفيس بوك - الجمعيات الدينية- وسائل الإعلام; Social networking sites - Religious awareness - Facebook - Religious associations - Media